Rosa Luxemburg Vive la lutte! : correspondance 1891-1914. - Luxemburg, Rosa; Wiell, Claudie; Badia, Gilbert; Haupt, Georges; Petit, Irène (Paris : Maspero, 1975)
Bibliotheek François Vercammen
Frans
Monografie